Model Jaringan Distribusi Produk dengan Pendekatan Fuzzy Multi Objective Programming - Viarani, Suci Oktri Viarani M; Henmaidi; Bronto Adi, Alexie Herryandie (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2018)
PT. Semen Padang is one of the cement producers competing to meet the needs of the cement. To that end, PT. Semen Padang must ensure the availability of cement on time, quantity, location and at competitive rates. One way to achieve this by optimizing the distribution system because it will be able to maximize sales and increase corporate profits. In this research, the distribution network planning model of PT. Semen Padang considering the cost of transportation, facility capacity, time, and uncertain demand. This model aims to minimize the total cost of product distribution and cost of opening the buffer warehouse and Packing Plant and maximize responsiveness to customers considering the uncertain parameters by using Fuzzy Multi-Objective Programming method. Based on the results of the research, had obtained the product distribution network planning model by using the fuzzy multi-objective programming method with the output is the opening of Packing Plant and buffer warehouse and the amount of product delivery to the final consumer with minimum cost and time of distribution. Search solution or output model assisted with Software Lingo 17.0. The designed model is able to explain the change of output if there are any changes in parameters covering demand between marketing areas, transportation costs between marketing areas and vehicle speed in transporting products from the last distribution center to the marketing area. The model can be implemented in the distribution network planning of PT. Semen Padang by using data in accordance with the conditions in the field.